Age of early specialization, competitive volume, injury, and sleep habits in youth sport: A preliminary study of us youth basketball - Meisel, P. L.; DiFiori, J. P.; Côté, J.; Nguyen, J. T.; Brenner, J. S.; Malina, R. M.; Ryan III, E.; Güllich, A. (Sports Health: A Multidisciplinary Approach, 2022)
Background: Concerns for youth sports in the United States often focus on early sport specialization, overemphasis on competition, injuries, and burnout. Little research has addressed relationships among the preceding and other concerns, including time away from organized sport, sleep, and perceptions of physical and psychological well-being. Hypothesis: There is an association between reported competitive gameplay volume and specialization, injury, and fatigue among elite youth basketball players. Study Design: Cross-sectional study; convenience sample. Level of Evidence: Level 4. Methods: An anonymous questionnaire was administered to a convenience sample of youth basketball players between 13 and 18 years of age from across the United States. Participants were queried about multiple factors, including the extent of their participation in organized basketball and other sports, time away from organized basketball, injury, sleep, and feelings of exhaustion related to basketball participation. Results: A total of 772 participants (145 girls, 627 boys) completed a survey. All participants played for a select or elite club basketball team and/or a high school basketball team. Overall, 49% played more than 50 games within the past year. A total of 73% were specialized in basketball, 58% prior to age 14 years, and 35% prior to age 11 years. In all, 70% reported less than 1 month away from organized basketball within the past year, and 28% reported no time away. A total of 54% reported sleeping less than the recommended 8 hours each night during the school year. Within the prior year, 55% reported feeling physically exhausted and 45% reported feeling mentally exhausted from basketball. Regression analysis did not find any significant relationships between early specialization prior to age 14 years and basketball-related injury or feelings of mental or physical exhaustion. Conclusion: In this select group of youth basketball players, the majority specialized in basketball prior to age 14 years and reported a large number of competitive events with little time away from organized basketball. Clinical Relevance: The results from a sample of highly competitive youth basketball players indicate issues that warrant further attention and research regarding the potential impact of specialization, frequent competitions, lack of time away from organized sport, and perceptions of well-being in young athletes.